Flexible and stable copper-based halide scintillator for high-performance X-ray imaging. Issue 95 (10th November 2022) - Wang, Baiqian; Jia, Zhenglin; Yang, Xin; Lu, Shirong; Zhao, Jinrong; Sun, Zhe; Qian, Qingkai; Lin, Qianqian; Zang, Zhigang
Abstract : A flexible scintillator screen of Rb2 CuBr3 @polymer has been developed for X-ray imaging with good quality, exhibiting a high spatial resolution of 27.9 lp mm −1 and a low detection limit of 63 nGyair s −1 . Abstract : Rb2 CuBr3 nanocrystals with a high photoluminescence quantum yield (PLQY) of 75% were synthesized and then further mixed with polymethyl methacrylate to form flexible scintillators. The scintillators maintain a high PLQY, even after bending for 2000 cycles and storing in air for 28 days. X-Ray imaging of targeted objects was demonstrated based on the flexible scintillators, which exhibits a detection limit of 63 nGyair s −1 and a spatial resolution of 27.9 lp mm −1 .